Holey Films: Freestanding NiFe Oxyfluoride Holey Film with Ultrahigh Volumetric Capacitance for Flexible Asymmetric Supercapacitors (Small 3/2018). Issue 3 (18th January 2018) - Liang, Kun; Marcus, Kyle; Yang, Zhenzhong; Zhou, Le; Pan, Hao; Bai, Yuanli; Du, Yingge; Engelhard, Mark H.; Yang, Yang
Abstract : In article1702295, Yang Yang and co‐workers fabricate a freestanding NiFe oxyfluoride holey film using a facile and scalable electrochemical route. The residual metal filaments inside the oxyfluoride make these freestanding electrodes mechanically robust, flexible and highly conductive, which is beneficial for flexible supercapacitors. Two‐electrode asymmetric supercapacitors assembled using the NiFe oxyfluoride holey films show a super high volumetric capacitance, and energy and power densities, making them promising candidates for flexible energy storage.